A novel high light-inducible carotenoid-binding protein complex in the thylakoid membranes of Synechocystis PCC 6803 - Daddy, Soumana (Sci Rep, 2015)
Synechocystis sp. PCC 6803 is a model cyanobacterium extensively used to study photosynthesis. Here we reveal a novel high light-inducible carotenoid-binding protein complex (HLCC) in the thylakoid membranes of Synechocystis PCC 6803 cells exposed to high intensity light. Zeaxanthin and myxoxanthophyll accounted for 29.8% and 54.8%, respectively, of the carotenoids bound to the complex. Using Blue-Native PAGE followed by 2D SDS-PAGE and mass spectrometry, we showed that the HLCC consisted of Slr1128, IsiA, PsaD, and HliA/B. We confirmed these findings by SEAD fluorescence cross-linking and anti-PsaD immuno-coprecipitation analyses. The expression of genes encoding the protein components of the HLCC was enhanced by high light illumination and artificial oxidative stress. Deletion of these proteins resulted in impaired state transition and increased sensitivity to oxidative and/or high light stress, as indicated by increased membrane peroxidation. Therefore, the HLCC protects thylakoid membranes from extensive photooxidative damage, likely via a mechanism involving state transition.